Intelligence and executive function are associated with age at insult, time post-insult, and disability following chronic pediatric acquired brain injury - Anne Elisabeth Brandt; Anne Elisabeth Brandt; Torstein B. Rø; Torstein B. Rø; Torun G. Finnanger; Ruth E. Hypher; Espen Lien; Bendik Lund; Bendik Lund; Cathy Catroppa; Cathy Catroppa; Cathy Catroppa; et al. (Frontiers in Neurology, 2024)
BackgroundPediatric acquired brain injury (pABI) profoundly affects cognitive functions, encompassing IQ and executive functions (EFs). Particularly, young age at insult may lead to persistent and debilitating deficits, affecting daily-life functioning negatively. This study delves into the intricate interplay of age at insult, time post-insult, and their associations with IQ and EFs during chronic (>1 year) pABI. Additionally, we investigate cognitive performance across different levels of global function, recognizing the multifaceted nature of developmental factors influencing outcomes.MethodsDrawing upon insult data and baseline information analyzing secondary outcomes from a multicenter RCT, including comprehensive medical and neuropsychological assessments of participants aged 10 to 17 years with pABI and parent-reported executive dysfunctions. The study examined associations between age at insult (early, EI; ≤7y vs. late, LI; > 7y) and time post-insult with IQ and EFs (updating, shifting, inhibition, and executive attention). Additionally, utilizing the Pediatric Glasgow Outcome Scale-Extended, we explored cognitive performance across levels of global functioning.ResultsSeventy-six participants, median 8 years at insult and 5 years post-insult, predominantly exhibiting moderate disability (n = 38), were included. Notably, participants with LI demonstrated superior IQ, executive attention, and shifting compared to EI, [adjusted mean differences with 95% Confidence Intervals (CIs); 7.9 (1.4, 14.4), 2.48 (0.71, 4.24) and 1.73 (0.03, 3.43), respectively]. Conversely, extended post-insult duration was associated with diminished performances, evident in mean differences with 95% CIs for IQ, updating, shifting, and executive attention compared to 1–2 years post-insult [−11.1 (−20.4, −1.7), −8.4 (−16.7, −0.1), −2.6 (−4.4, −0.7), −2.9 (−4.5, −1.2), −3.8 (−6.4, −1.3), −2.6 (−5.0, −0.3), and −3.2 (−5.7, −0.8)]. Global function exhibited a robust relationship with IQ and EFs.ConclusionEarly insults and prolonged post-insult durations impose lasting tribulations in chronic pABI. While confirmation through larger studies is needed, these findings carry clinical implications, underscoring the importance of vigilance regarding early insults. Moreover, they dispel the notion that children fully recover from pABI; instead, they advocate equitable rehabilitation offerings for pABI, tailored to address cognitive functions, recognizing their pivotal role in achieving independence and participation in society. Incorporating disability screening in long-term follow-up assessments may prove beneficial.